The qualifying exam for general practitioners and the physicians' registry in the early Meiji period - Teruo Higuchi (Elsevier, 2010)
The introduction into Japan of Western science, including medicine, began in the latter half of the 18th century. By mid-19th century, Western medicine had not only spread to the principal cities but had also gradually become established in outlying districts. With the advent of the new Meiji government in 1868, the nation as a whole came under one centralized government, which quickly turned its attention to the creation of a system for healthcare and public hygiene. The aim was not merely to treat individual illness but also to secure medical practitioners who would be responsible for the practical aspects of preventing the spread of contagious diseases, carrying out inspections at the ports open to foreign vessels, and attending to matters concerning birth and death. To achieve that goal, in 1884 the government moved ahead of other countries in assuming national control in the establishment of a qualifying examination for general practitioners and a system for registering physicians. Working with public records from the National Archives of Japan and other sources, I here give an outline of the development of the healthcare system in the early Meiji period.